Contextualized ubiquity: a new opportunity for rendering business information and services - Cunha, Carlos R. (2010)
Stating that information and services are ubiquitous, means that they are available anywhere, anytime. The development of mobile-devices with wireless network-access capabilities, together with the decrease in network-traffic costs and the proliferation of free wireless hotspots, makes the use of mobile-devices, as Internet access tools, increasingly common and attractive. With novel forms of presenting information and to provide new ways to interact with consumers, new business strategies can be boosted, in Customer Relationship Management (CRM) and m-commerce. This paper describes a different approach to the relationship between customers and business-providers, based on contextualization mechanisms located in commercial products, which in turn acts as a gateway to static tag-embedded information as well as web-based information and services. A wine integrated management system, called SIGPV, is presented as a proof-of-concept, enumerating some of possible major business and CRM benefits.